2019
DOI: 10.1039/c9nr05944j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning two-dimensional phase formation through epitaxial strain and growth conditions: silica and silicate on NixPd1−x(111) alloy substrates

Abstract: The combined experimental and theoretical results demonstrate the manipulation of 2D VDW silica and 2D Ni silicate through growth conditions, and the determination of the maximum epitaxial strain imparted to the 2D system through alloy substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…The experimental realisation of monolayer Kagome silicates can be dated back to the 1990s 43 , but more recently various synthesis strategies have been developed to obtain 2D Kagome silicate or silica on multiple substrates [44][45][46][47][48] . These developments enable researchers to study the structural [49][50][51][52][53][54][55] , vibrational [56][57][58] , electronic [59][60][61] , mechanical 62,63 , and chemical properties 64 of this material family and to explore the various physical phenomena associated with 2D Kagome lattices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental realisation of monolayer Kagome silicates can be dated back to the 1990s 43 , but more recently various synthesis strategies have been developed to obtain 2D Kagome silicate or silica on multiple substrates [44][45][46][47][48] . These developments enable researchers to study the structural [49][50][51][52][53][54][55] , vibrational [56][57][58] , electronic [59][60][61] , mechanical 62,63 , and chemical properties 64 of this material family and to explore the various physical phenomena associated with 2D Kagome lattices.…”
Section: Resultsmentioning
confidence: 99%
“…56 , and structural relaxation at different electric fields always removes the rotation distortion. Experimentally it has been found that both monolayer silicate and bilayer silica can be grown on various substrates with biaxial strains varying from −5.6 to 5.7% 44,48,52,53,64,65 . In addition, theoretical calculations have shown that defect-free 2D silica can be deformed up to a maximum strain of 10.4%, while for defective samples no abrupt material failure is observed at strains around 7.8-8.1% 63 .…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Altman et al, the lattice mismatch is vital to controlling bilayer silica structures. , The incorporation of the Al 3+ ion then provides an additional possibility for structure control via strain. However, the appearance of the amorphous phase and the spatial variations in the Al concentration remain challenges that must be surmounted in the preparation of specifically desired aluminosilicates.…”
Section: Chemical Modifications Of the 2d-silicamentioning
confidence: 99%
“…We recall that highly crystalline BL silica films can be grown on Ni x Pd 1– x (111) alloy surfaces with a continuously tunable lattice constant . Altman and co-workers further showed that the reactions of Si and O with the Ni x Pd 1– x (111) alloy surface would extract Ni atoms from the substrate to form 2D Ni-silicates. , …”
Section: Chemical Modifications Of the 2d-silicamentioning
confidence: 99%
See 1 more Smart Citation